2021
DOI: 10.1186/s12888-021-03579-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral group treatment for low self-esteem in psychosis: a proof of concept study

Abstract: Background Patients with a psychotic disorder often suffer from low self-esteem, which has been related to higher suicidal risk, poor quality of life and, the maintenance of psychotic and depression symptoms. However, intervention studies are scarce and reported interventions concern individual therapies provided by highly educated psychologists. Both the individual setting and the required qualifications of the therapist may contribute to a low level of availability of an intervention. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Similar to former studies, our study has shown that the rapid recovery of cognition facilitated by the TEAS intervention can significantly reverse the decline in quality of life, especially in terms of improved global function, emotional function, fatigue, and pain scores, even at 6 months [ 32 ]. It was consistent with previous observations that good cognitive function could help patients improve their self-esteem, set goals in their lives, and enjoy activities that help them to achieve better mental health [ 33 ]. In addition, this study was in agreement with previous research showing that TEAS could alleviate acute pain and prevent its transition to chronic pain after surgery [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to former studies, our study has shown that the rapid recovery of cognition facilitated by the TEAS intervention can significantly reverse the decline in quality of life, especially in terms of improved global function, emotional function, fatigue, and pain scores, even at 6 months [ 32 ]. It was consistent with previous observations that good cognitive function could help patients improve their self-esteem, set goals in their lives, and enjoy activities that help them to achieve better mental health [ 33 ]. In addition, this study was in agreement with previous research showing that TEAS could alleviate acute pain and prevent its transition to chronic pain after surgery [ 34 ].…”
Section: Discussionsupporting
confidence: 91%